Penerapan IoT pada Keamanan Lingkungan Berbasis Android - Hadriansa Hadriansa; Denis Prayogi (Jurnal Media Infotama, 2025)
The development of information and communication technology (ICT), especially the Internet of Things (IoT), has changed human interaction with the surrounding environment. IoT allows physical devices to connect and communicate over the internet, improving efficiency and security in various areas, including public safety. This research focuses on the development of an IoT-based Citizen Security System, which integrates the active participation of citizens in the environmental security system through the Environmental Security and Order System (Siskamling). Prototypes developed using the ESP32 Module are connected to a database to detect potential hazards, such as theft or fire. This tool allows homeowners to send emergency signals through a panic button that is directly connected to the kamling post. In addition, the system provides information about the schedule of the kamling post to residents. This study shows that this device functions manually and provides notifications to residents and kamling post officers through an Android application. With additional features such as RTC for time counting and buzzer as an alarm, the system is expected to increase awareness and response to emergency situations in the environment. The conclusion shows the significant potential of IoT technology in strengthening community security.